2015
DOI: 10.1016/j.ultramic.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of detector dead-time on quantitative analyses involving boron and multi-hit detection events in atom probe tomography

Abstract: In atom probe tomography (APT), some elements tend to field evaporate preferentially in multi-hit detection events. Boron (B) is one such element. It is thought that a large fraction of the B signal may be lost during data acquisition and is not reported in the mass spectrum or in the 3-D APT reconstruction. Understanding the relationship between the field evaporation behavior of B and the limitations for detecting multi-hit events can provide insight into the signal loss mechanism for B and may suggest ways t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 51 publications
(114 reference statements)
5
63
0
Order By: Relevance
“…However, while gross differences between elemental sensitivities are avoided, more subtle effects can still be present and may result in chemical or isotopic compositional biases. The position‐sensitive detector has some dead time associated with the impact of each ion, so that a high flux of multiple‐ion events will lead to a loss of data, which may preference particular mass peaks (Thuvander et al , , Meisenkothen et al , Thuvander et al ). The precise nature of the dead time, which may include spatial proximity as well as coincidence limits, can be complex and will depend on the specific construction of the detector hardware (Peng et al ).…”
Section: Performance and Optimisationsmentioning
confidence: 99%
“…However, while gross differences between elemental sensitivities are avoided, more subtle effects can still be present and may result in chemical or isotopic compositional biases. The position‐sensitive detector has some dead time associated with the impact of each ion, so that a high flux of multiple‐ion events will lead to a loss of data, which may preference particular mass peaks (Thuvander et al , , Meisenkothen et al , Thuvander et al ). The precise nature of the dead time, which may include spatial proximity as well as coincidence limits, can be complex and will depend on the specific construction of the detector hardware (Peng et al ).…”
Section: Performance and Optimisationsmentioning
confidence: 99%
“…This region is called the dead zone and the period of time is called the dead time. They are related in such a way that the dead time decreases with distance from the detection event [37]. If a second ion hit the detector within the dead zone, at most one ion will be detected.…”
Section: Delay--line Detector and Multiple Eventsmentioning
confidence: 99%
“…The most common dopant elements in the silicon semiconductors are B (for p‐doping) and P (for n‐doping). Although there are a few APT studies of B quantification, only Meisenkothen et al reported there is 20% to 36% B signal lost in B implanted (B dose of 1.5e15 atoms/cm 2 ) of Si standard sample. It is well understood that B determined by the APT is always smaller than the SIMS value, but the loading dependence on concentration is not established yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, deviation was as small as 14% in the low dose sample of 1.20e14 atoms/cm 2 . The data of Meisenkothen et al6 were plotted in the same figure for comparison…”
mentioning
confidence: 99%